2018
DOI: 10.1097/shk.0000000000000998
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment With Argon Protects Human Cardiac Myocyte-Like Progenitor Cells from Oxygen Glucose Deprivation-Induced Cell Death by Activation of AKT and Differential Regulation of Mapkinases

Abstract: Pretreatment with argon protects HCMs from apoptosis under ischemic conditions via activation of Akt, Erk, and biphasic regulation of JNK. Argon gas is cheap and easily administrable, and might be a novel therapy to reduce myocardial ischemia-reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
12
0
2
Order By: Relevance
“…Previous studies have shown that inert gas argon pre-treatment influences OGD-induced oxidative damage of human cardiomyocytes. Qi et al reported that cardiomyocytes pre-treated with 30% argon for 90 min significantly increased cell activity and inhibited apoptosis [ 4 ]. In the present study, after pre-treatment with 50% argon for 1 h, the viability of cardiomyocytes induced by OGD increased and the apoptosis rate decreased significantly, which was similar to previous results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that inert gas argon pre-treatment influences OGD-induced oxidative damage of human cardiomyocytes. Qi et al reported that cardiomyocytes pre-treated with 30% argon for 90 min significantly increased cell activity and inhibited apoptosis [ 4 ]. In the present study, after pre-treatment with 50% argon for 1 h, the viability of cardiomyocytes induced by OGD increased and the apoptosis rate decreased significantly, which was similar to previous results.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, inert gas has become a research hotspot because of its potential organ protective effect. Argon, as one of the main components, has a protective effect on nerves and myocardium after ischemia reperfusion injury [3][4][5][6]. In vivo, 30% and 50% argon pre-treatment significantly reduced the apoptosis and inflammation level and improved the cell survival rate in human cardiomyocytes by AKT activation and differential regulation of MAP kinases [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, finding a new approach to prolong the survival rate of CPCs to improve the host cardiac function is an important challenge for researchers. Various approaches have been used to overcome this problem, including preconditioning stem cells by genetic or pharmacologic manipulations or exposing them to in vitro conditions that mimic the harsh environment of an ischemic heart, such as preconditioning with cobalt protoporphyrin in CSCs [21], cobalt chloride in human ESCs [22], pioglitazone in MSCs [23], argon in human cardiac myocyte-like progenitor cells [24], overexpression of Pim-1 in hCPCs [25], and pretreatment of CSCs with MSC exosome [26]. Although all of these approaches showed a potential role in improving cardiac function, the quantitative comparison of transplanted cells in the host heart and their antiapoptosis and pro-angiogenesis effect has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The protective value of noble gases for the ex vivo preservation of organs prior to transplant and IRI during the perioperative period has been extensively verified in numerous preclinical experiments and clinical trials, with reports concerning argon and xenon being the most common (48)(49)(50)(51). In a rat spinal I/R experimental model by Liu et al (52), the rats in the I/R group with xenon-delayed post-conditioning had higher neurological scores, more normal motor neurons, fewer apoptotic neurons, and significantly higher levels of Akt and extracellular signalregulated kinase (ERK) than those without xenon-delayed post-conditioning, suggesting that xenon attenuated spinal cord IRI by activating the Akt and ERK signaling pathways.…”
Section: Noble Gasesmentioning
confidence: 99%